Teacher's Strategy in Improving Student Motivation - Popy Wulandari (Yayasan Bayt Shufiya Nusantara, 2024)
This study aims to determine the effectiveness of learning strategies used by teachers in increasing student learning motivation in Jurisprudence subjects at MAN 1 Serdang Bedagai. This research uses a quantitative approach with a survey method. Data were collected through distributing questionnaires to 34 students as respondents. The results of the analysis show that the strategies applied by teachers are considered effective in increasing students' learning motivation. These strategies include the habituation of prayer before learning, the implementation of ice breaking to break the atmosphere, the use of unique and easy-to-understand material delivery methods, and the provision of educational game-based assignments. This finding confirms that the application of creative, varied and responsive strategies to students' needs can be an important instrument in encouraging enthusiasm for learning and improving the quality of learning in the classroom.